Kinetic and Electrochemical Reaction Mechanism Investigations of Rodlike CoMoO4 Anode Material for Sodium-Ion Batteries - Ali, Ghulam; Islam, Mobinul; Kim, Ji Young; Jung, Hun-Gi; Chung, Kyung Yoon (American Chemical Society, 2019)
Sodium-ion batteries are considered the most promising power source for electrical energy storage systems because of the abundance of sodium and their significant cost advantages. However, high-performance electrode materials are required for their successful application. Herein, we report a monoclinic-type CoMoO4 material which is synthesized by a simple solution method. An optimized calcination temperature with a high crystallinity and a rodlike morphology of the material are selected after analyzing the as-synthesized powder by temperature-dependent time-resolved X-ray diffraction. The CoMoO4 rods exhibit initial discharge and charge capacities of 537 and 410 mA h g(-1), respectively, when used as an anode for sodium-ion batteries. The sodium diffusion coefficient in the bimetallic CoMoO4 anode is measured using the galvanostatic intermittent titration technique and calculated in the range of 1.565 x 10(-15) to 4.447 x 10(-18) cm(2) s(-1) during the initial cycle. Further, the reaction mechanism is investigated using ex situ X-ray diffraction and X-ray absorption spectroscopy, and the obtained results suggest an amorphous like structure and reduction/oxidation of Co and Mo during the sodium insertion/extraction process. Ex situ transmission electron microscopy and energy-dispersive spectroscopy images of the CoMoO4 anode in fully discharged and recharged state reveal the rodlike morphology with homogenous element distribution.
Keywords: HIGH-CAPACITY ANODE; RAY-ABSORPTION SPECTROSCOPY; HIGH-PERFORMANCE ANODE; NEGATIVE ELECTRODES; LITHIUM; COMPOSITE; NANOPARTICLES; TRANSITION; NANOWIRES; METALS